2020
DOI: 10.3390/toxins12080485
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Specific Venom Variation in the Australian Coastal Taipan Oxyuranus scutellatus

Abstract: Intra-specific venom variation has the potential to provide important insights into the evolution of snake venom, but remains a relatively neglected aspect of snake venom studies. We investigated the venom from 13 individual coastal taipans Oxyuranus scutellatus from four localities on the north-east coast of Australia, spanning a distance of 2000 km. The intra-specific variation in taipan venom was considerably less than the inter-specific variation between it and the other Australian elapids to which it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Unlike the other samples, our B. asper Mexican samples were individual venoms rather than pooled venoms ( Table 7 ). Individual venom variation has been observed in multiple snake species [ 49 , 50 , 51 ]; thus pooled venoms are favoured as they help account for any possible variation between individuals. Therefore, in the present study, individual variation cannot be ruled out as contributing to the observed variation in venom potency and antivenom efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the other samples, our B. asper Mexican samples were individual venoms rather than pooled venoms ( Table 7 ). Individual venom variation has been observed in multiple snake species [ 49 , 50 , 51 ]; thus pooled venoms are favoured as they help account for any possible variation between individuals. Therefore, in the present study, individual variation cannot be ruled out as contributing to the observed variation in venom potency and antivenom efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Snake venom can vary in composition at all taxonomic levels; families, clades, genera, species (inter-specific variation) and within species (intra-specific or inter-population variation (Saviola et al 2017)). The expression of different protein families can also vary within populations (intra-population variation) (Tasoulis et al 2020b). Venom composition can also vary in a number of ways, including different relative amounts of each protein family, different numbers of toxins within each protein family and different types of toxins with each protein family (amino acid sequence differences).…”
Section: Types and Levels Of Venom Variationmentioning
confidence: 99%
“…It has proven to be very useful in separating proteins, due to the technique's ability to separate native proteins (undigested) or protein complexes. This is essential in the field of venomics, as toxins are often large proteins that may or may not exist in complexes with other proteins [48,49]. This technique can also be achieved using HPLC to perform a high-resolution fractionation of molecules based on their molecular weight [47].…”
Section: Separation Techniquesmentioning
confidence: 99%